2019
DOI: 10.3389/frobt.2019.00010
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Parameter Settings on the Benefits of Robot-to-Robot Learning in Evolutionary Robotics

Abstract: Robot-to-robot learning, a specific case of social learning in robotics, enables multiple robots to share learned skills while completing a task. The literature offers various statements of its benefits. Robots using this type of social learning can reach a higher performance, an increased learning speed, or both, compared to robots using individual learning only. No general explanation has been advanced for the difference in observations, which make the results highly dependent on the particular system and pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
1
1
0
Order By: Relevance
“…Even more importantly, we have also shown that, as expected, social learning provides increased learning speed, but also yields increased performance when compared to individual learning [95]. This is due to the possibility of running several instances of individual learning algorithm with different meta-parameters values, as best values cannot be guessed before run-time.…”
Section: From One Agent To Anothersupporting
confidence: 64%
“…Even more importantly, we have also shown that, as expected, social learning provides increased learning speed, but also yields increased performance when compared to individual learning [95]. This is due to the possibility of running several instances of individual learning algorithm with different meta-parameters values, as best values cannot be guessed before run-time.…”
Section: From One Agent To Anothersupporting
confidence: 64%
“…For a communication system to emerge, it is possible to use the evolutionary robotics (ER) approach (Bredeche et al, 2018). In ER the morphological and / or control structures are the result of the iterative pressure conducted by an artificial evolutionary process (Heinerman et al 2019;Nolfi, 1998). A common representation of control systems in ER are artificial neural networks (ANN) optimized by evolutionary algorithms (Alattas et al, 2019), such as Genetic Algorithms (GA) (Baldominos et al, 2020).…”
Section: Introductionmentioning
confidence: 99%